The Influence of The Cooperative Learning Model Assisted by Interactive PowerPoint On The Learning Outcomes of Science In The Material of Kingdoms In The Archipelago for Grade IV Elementary Schools - Farida Nur Rodhiyatul Azizah; Desty Dwi Rochmania (Universitas Nusantara PGRI Kediri, 2026)
Science learning on history material, especially about kingdoms in the Indonesian archipelago, still shows a gap between the philosophical objectives of the curriculum and its implementation in the classroom. One effort to improve student learning outcomes is to implement the Cooperative Learning model supported by interactive PowerPoint. This study aims to test the effect of the use of this media-assisted model on the learning outcomes of fourth-grade students on the material of kingdoms in the Indonesian archipelago. The method used was a quasi-experimental design with a nonequivalent control group. The research sample consisted of 47 students and was taken through a total sampling technique. Data analysis was carried out through descriptive statistics, the N-Gain test, and inferential analysis. The test results showed a significance value <0.001 which is smaller than 0.05, so it can be concluded that the application of the Cooperative Learning model assisted by interactive PowerPoint has a significant effect in improving student learning outcomes in science learning on the material of kingdoms in the Indonesian archipelago.